Discovery of a novel spin-polarized nodal ring in a two-dimensional HK lattice. Issue 44 (7th November 2018) - Zhang, Liang; Zhang, Shu-feng; Ji, Wei-xiao; Zhang, Chang-wen; Li, Ping; Wang, Pei-ji; Li, Sheng-shi; Yan, Shi-shen
Abstract : Nodal-ring materials with a spin-polarized feature have attracted intensive interest recently due to their exotic properties and potential applications in spintronics. Abstract : Nodal-ring materials with a spin-polarized feature have attracted intensive interest recently due to their exotic properties and potential applications in spintronics. However, such a type of two-dimensional (2D) lattice is rather rare and difficult to realize experimentally. Here, we identify the first 2D Honeycomb-Kagome (HK) lattice, Mn–Cyanogen, as a new single-spin nodal-ring material by using first-principles calculations. Mn–Cyanogen shows gapless and semiconducting properties in spin-up and spin-down orientations, respectively, indicating a spin-gapless semiconductor nature. Remarkably, a spin-polarized nodal ring induced by p x, y /p z band inversion is captured from the 3D band structure, which is irrelevant to spin–orbit coupling. The origin of the single-spin nodal-ring can be further clarified by the effective tight-binding (TB) model. These results open a new avenue to achieving spin-polarized nodal-ring materials with promising applications in spintronic devices.